2018
DOI: 10.1016/j.ajpath.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption Ionization Mapping of Lysophosphatidic Acid Changes after Traumatic Brain Injury and the Relationship to Cellular Pathology

Abstract: Lysophosphatidic acid (LPA) levels increase in the cerebrospinal fluid and blood within 24 hours after traumatic brain injury (TBI), indicating it may be a biomarker for subsequent cellular pathology. However, no data exist that document this association after TBI. We, therefore, acquired matrix-assisted laser desorption ionization imaging mass spectrometry data of LPA, major LPA metabolites, and hemoglobin from adult rat brains at 1 and 3 hours after controlled cortical impact injury. Data were semiquantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…LPAs are a bioactive component of oxLDL, which show a positive correlation with CSF levels of Aβ [48]. Moreover, traumatic brain injury (TBI) patients also exhibit increased CSF levels of LPAs [49]. Because amyloid pathology is observed in nearly 30% of TBI patients with unknown mechanisms [50], our observed positive association of amyloid pathology and LPA may suggest the role of LPAs as a mediator in the aggregation of amyloid pathology, which needs further investigation.…”
Section: Discussionmentioning
confidence: 81%
“…LPAs are a bioactive component of oxLDL, which show a positive correlation with CSF levels of Aβ [48]. Moreover, traumatic brain injury (TBI) patients also exhibit increased CSF levels of LPAs [49]. Because amyloid pathology is observed in nearly 30% of TBI patients with unknown mechanisms [50], our observed positive association of amyloid pathology and LPA may suggest the role of LPAs as a mediator in the aggregation of amyloid pathology, which needs further investigation.…”
Section: Discussionmentioning
confidence: 81%
“… 160 Using a rat model of neurotrauma, Mcdonald and coworkers demonstrated that LPA increases diffusely after the injury, whereas LPA metabolites increases in white matter, in the hemorrhagic pericontused gray matter regions both LPA and its metabolites were increased, these events results in axonal injury and cell death, especially in the white matter. 161 …”
Section: Lpa and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In patients, LPA levels increases in the blood and CSF within 24 h in TBI patients, indicating that LPA could possibly be one of the first mediators responding to the injury and suggesting it may be a biomarker for subsequent cellular pathology. 161 …”
Section: Lpa and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The same search filters were applied, leading to 295 results being excluded while a further 71 duplicates were removed using EndNote 20 [ 30 ]. A total of 140 papers were manually excluded following assessment against the selection criteria, leaving a total of 24 papers eligible for inclusion in the review [ 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Figure 2 provides an overview of the protein literature search and study selection process.…”
Section: Resultsmentioning
confidence: 99%